The Intercropping Soybean (Glycine max L.) with Sorghum [Sorghum bicolor (L.) Moench] in East Hararghe, Oromia - Umata, Habte Berhanu; Tadese, Fiqadu; Abro, Husen (Central Research Institute For Agriculture, 2024)
Field experiments were done in 2018 and 2019 at Fedis and Erer to determine the effect of intercropping sorghum with soybean on grain yield. Seed yields were higher in the sole crops of sorghum and soybean than in the individual components of the intercrops. This is due to the crops' compete of nutrients, light, water, and other factors. The yields of the intercrop's component crops varied greatly depending on the variety. The sorghum/soybean ‘Teshale/Awasa-95’ intercrops were more productive than the sorghum/soybean ‘Dhaqaba/Awasa-95’ intercrops, which had an LER (land equivalent ratio) of 1.14. Intercropping sorghum ‘Teshale’ with soybean ‘Awasa-95’ resulted in maximum grain production and LER greater than one, showing that intercropping has an advantage over solely planting. As a result, intercropping sorghum and soybean is compatible, desirable, and more advantageous for increasing production than solely cropping under the same conditions.